Reindeer mortality in Finland during the years 1971-81 - Nieminen, Mauri; Koskela, Kirsti; Koivuperä, Niilo (Rangifer, 1982)
During the reindeer herding years 1975/76—1979/80 the percentage of calves in the autumn troughout the whole reindeer herding area was on average 61% (range 53—69%). The lowest calf percentages were found in the Salla (42%), Orajarvi (40%), Kallioluoma (48%) and Muonio (48%) reindeer association areas. The highest calf percentage were in the Kasivarsi (89%), Kiiminki (86%), Hammastunturi (84%) and Halla (75%) areas. According to statistics in the whole reindeer herding area a total of 115 382 reindeer were lost in the herding years 1971/72—1980/81. However, the increase during the same period was 166 899 so that the number of reindeer grew by 51 507. The number of reindeer (adults and calves) reduced in 14 and increased in 42 reindeer association areas. There were 48 severe losses (loss over 20%) and in average losses (loss percentage 15.6%, total loss 35.6%) the number of reindeer in the association decreased to 64.4% of the previous two year's average figure. There were six losses where the number of reindeer decreased more than 50%. A total of 39 923 reindeer were lost and of those 23 501 were lost in 1973/74 alone. Highest losses were suffered by certain of the northern herding associations. In the years 1976—80, 12 147 reindeer died in traffic accidents and of those 10 049 (82.7%) were run over by cars and 2 108 (17.7%) by trains. On average over 100 reindeer died annually due to traffic in Kallioluoma, Orajarvi, Pudasjarvi and Palojarvi reindeer herding areas. The worst section of road was route No. 80 between Vikajarvi and Kemijarvi and of rail kilometer section 780—850 from Ii to Kemi. In winter most reindeer died in traffic in January—February and in summer i July. Predators killed a total of 7 5 72 reindeer throughout the whole reindeer herding area during 1976—81. Predator damage was mainly concentrated in the eastern reindeer herding association areas and predators killed on average 155 reindeer in the Kasivarsi (range 100—196), 123 reindeer in the Lapland (range 20—201) and 119 reindeer in the Sallivaara (range 31—208) herding areas. Wolves killed most reindeer (2 265 reindeer, 29.9%), second came bears (1 876 reindeer, 24.8%), wolverine (1 767 reindeer, 23.4%) and lynx (252 reindeer, 3.3%). Porokuolemat Suomessa vuosina 1971—81. Abstract in Finnish / Yhteenveto: Poronhoitovuosina 1975/76 - 1979/80 vasaprosentti oli syksyllå koko poronhoitoalueella keskimåårin 61% (vaihtelu 53—69%). Alhaisimmat vasaprosentit tavattiin Sallan (42%), Orajårven (46%), Kallioluoman (48%) ja Muonion paliskunnissa (48%). Korkeimmat vasaprosentit olivat Kårivarren (89%), Kiimingin (86%), Hammastunturin (84%) ja Hallan (75%) paliskunnissa. Poronhoitovuosina 1971/72 - 1980/81 menetettiin tilastojen mukaan koko poronhoitoalueella yhteenså 115 382poroa. Lisåystå oli kuitenkin samanaikaisesti 166 889 poroa, joten poromåårå kasvoi 51 507 porolla. Poromåårå (lukuporot ja vasat) våheni 14 ja lisååntyi 42 paliskunnassa. Varsinaisia katoja (kato yli 20%) oli 48 ja keskimååråisesså kadossa (katoprosentti 15.6%, koko kato 35.6%) paliskunnan poroluku laski 64.4%: iin kahden edellisen vuoden keskiarvosta. Katoja, joissa poroluku tipahti yli 50%, oli kuusi. Kadoissa menetettiin yhteenså 39 923 poroa, joista jo vuoden 1973/74 kadossa 23 501 poroa (58.9%). Eniten kadoista kårsivåt erååt pohjoiset paliskunnat. Vuosina 1976—80 kuoli liikenteesså yhteenså 12 147 poroa, joista auton alle jåi 10 049 poroa (82.7%) ja junan alle 2 108 poroa (17.3%). Keskimåårin yli 100 poroa kuoli vuosittain liikenteesså Kallioluoman, Orajårven, Pudasjårven ja Palojårven paliskunnissa. Pahin maantieosuus oli kantatie n:o 80 vålillå Vikajårvi-Kemijårvi, ja rautatieosuus vålillå 780—850 ratakilometriå Iistå Kemiin. Eniten poroja kuoli liikenteesså talvella tammi-helmikuussa ja kesållå heinåkuussa. Pedot tappoivat vuosina 1976—81 yhteenså 7572 poroa koko poronhoitoalueella. Petovahingot keskittyivåt låhinnå itårajan paliskuntiin, ja pedot tappoivat vuosittain keskimåårin 155 poroa Kåsivarren (vaihtelu 100—196 poroa), 123 poroa Lapin (vaihtelu 20—201 poroa) ja 119 poroa Sallivaaran (vaihtelu 31—208 poroa) paliskunnissa. Eniten poroja tappoi susi (2265 poroa, 29.9%), seuraavaksi eniten karhu (1876 poroa, 24.8%), ahma (1176 poroa, 23.4%) ja ilves (252 poroa, 3.3%). Rendödeligheten i Finnland under åren 1971-81. Abstract in Swedish / Sammandrag: Under renskotselåren 1975/76 — 1979/80 var det procemuella antalet renkalvar 61% (variering 53—69%) inom hela renskotselområdet. De lågsta procentantalen for kalvar påtråffades inom renbeteslagen i Salla (42%), Orajårvi (46%), Kallioluoma (49%) och Muonio (48%). Det hogsta procentantalet for kalvar påtraffades inom renbeteslagen i Kåsivarsi (89%), Kiiminki (86%), Hammastunturi (84%) och Halla (75%). Under renskotselåren 1971/72 — 1980/81 forlorades inom hela renskotselområdet enligt statistiken sammanlagt 115 382 renar. Under samma period forekom dock en okning av 166 889 renar. Antalet renar okade alltså med 51 507. Antalet renar (inråknade renar och kalvar) minskade inom 14 renbeteslag och okade inom 42. Det forekom 48 verklig stora forluster (forlust mer ån 20%) och vid en forlust av medelstorlek (forlustprocent 15.6, totalforlust 35.6%) sjonk antalet renar inom renbeteslaget till 64.4% från medeltalet av de två foregående åren. Sammanlagt sex stora forluster intråffade varvid renarnas antal minskade med mer ån 50%. Sammanlagt 39 923 renar forlorades varvid antalet dodade renar steg redan under åren 1973/74 till 23 501 (58.9%). Vissa nordliga renbeteslag drabbades hårdast av dessa forluster. Under åren 1976—1980 dodades sammanlagt 12 147 av trafiken, av dessa 10 049 (82.7%) av bil och 2 108 (17.3%) av tåg. Trafiken dodade i medeltal mer an 100 renar inom renbeteslagen i Kallioluoma, Orajårvi, Pudasjårvi och Palojårvi. Den farligaste stråckan av landsvågen visade sig vara stamvåg nr. 80 mellan Vikajårvi och Kemijårvi samt av jårnvågen 780—850 bankilometer från Ijo till Kemijårvi. De fiesta trafikdodsfallen intråffade på vintern under januari—februari och på sommaren under juli månad. Inom hela renskotselområdet påtråffades under åren 1976—1981 sammanlagt 7 572 renar som rivits till dods av rovdjur. Rovdjurskadorna koncentrerade sig huvidsakligen till renbeteslagen på ostergrånsen. Sålunda dodades av rovdjur i medeltal 155 renar inom renbeteslagen i Kåsivarsi (variering 100—196 renar), 123 inom Lappi renbeteslagen (variering 20—201 renar). Mest dodades renar av varg (2 265 renar, 29.9%), sedan av bjorn (1876 renar, 24.8%), av jårv (1 767 renar, 23.4%) och av lodjur (252 renar, 3.3%).